Mapping the Slopes' Geomorphological Classification Using Geomatics Techniques: A Case Study of Zawita, Iraq - Mohammed Abbas Jaber Al-humairi1, Elaf Amer Majeed Alyasiri2* ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The aim of this present study is to classify and map the landscape of Zawita, Iraq. Different classification methods of the slope characteristics were considered such as slope degree, slope arching, slope direction, slope direction, hills shade, young classification, Demek classification. Digital Elevation Model was downloaded from USGS (2022) and applied as input data to classify and analyze the slope. The finding out that the area is identified as an elevated area. The elevation of the area is ranged between 520-1500 meters above sea level, which indicate the intensity and effectiveness of the alpine movements. Among analyzing the maps, the area is considered as arisky and sensitive to geomorphological hazards which made the area unstable. Most of the slopes of the study area is ranged from 2-34.9 degrees and this different degree of slopes is a consequent risk of high erosion